Controlling Protein Enrichment in Lipid Sponge Phase Droplets using SNAP‐Tag Bioconjugation. (19th January 2022) - Moinpour, Mahta; Fracassi, Alessandro; Brea, Roberto J.; Salvador‐Castell, Marta; Pandey, Sudip; Edwards, Madison M.; Seifert, Soenke; Joseph, Simpson; Sinha, Sunil K.; Devaraj, Neal K.
Abstract: All cells use organized lipid compartments to facilitate specific biological functions. Membrane‐bound organelles create defined spatial environments that favor unique chemical reactions while isolating incompatible biological processes. Despite the fundamental role of cellular organelles, there is a scarcity of methods for preparing functional artificial lipid‐based compartments. Here, we demonstrate a robust bioconjugation system for sequestering proteins into zwitterionic lipid sponge phase droplets. Incorporation of benzylguanine (BG)‐modified phospholipids that form stable covalent linkages with an O 6 ‐methylguanine DNA methyltransferase (SNAP‐tag) fusion protein enables programmable control of protein capture. We show that this methodology can be used to anchor hydrophilic proteins at the lipid‐aqueous interface, concentrating them within an accessible but protected chemical environment. SNAP‐tag technology enables the integration of proteins that regulate complex biological functions in lipid sponge phase droplets, and should facilitate the development of advanced lipid‐based artificial organelles. Abstract : A one‐step SNAP‐tag bioconjugation strategy for controlling protein capture in lipid sponge phase droplets is described. The approach provides a stable covalent bond between the protein of interest and the lipid bilayer of sponge droplets, enabling protein sequestration even in the presence of the complex biochemical machinery required for cell‐free protein expression.